XML for Dummies 4th Edition - Dykes, Lucinda (Wiley Publishing, 2011)
Create consistency on the Web, or tag your data for different purposesTag -- XML is it! XML tags let you share your format as well as your data, and this handy guide will show you how. You'll soon be using this markup language to create everything from Web sites to business forms, discovering schemas and DOC type, wandering the Xpath, teaming up XML with Office 2003, and more.